1983
DOI: 10.1088/0022-3727/16/5/012
|View full text |Cite
|
Sign up to set email alerts
|

DC nozzle arcs with mild wall ablation

Abstract: Recent experimental results (Smith et. al., 1980 and New land et. al., 1982) indicate that nozzle wall ablation can occur even before the arcing current reaches its thermal blocking limit. The wall ablation is caused by intense arc radiation. The evaporated wall material forms an ablation layer which reduces the effective flow area for the arc quenching gas. A theoretical model is established to study the complicated interaction between the ablation layer, the external gas flow and the arc. It has been found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Radiation loss which escapes from the arc near the nozzle exit at 3 kA is less than 15% of local Ohmic input. Radiation induced Teflon ablation is unlikely as at this power level (approximately 2 x 10 6 W/m with the exit electrical field given in figure 9(b)) Teflon will not reach its melting point for the experimental duration of 7 ms [45]. The measured arc voltage at 3 kA (figure 8) remains the same as that of 2 kA within experimental error, which indicates that ablation is unlikely to take place.…”
Section: Characteristics Of Nozzle Air Arc With Radiation Dominated Amentioning
confidence: 77%
“…Radiation loss which escapes from the arc near the nozzle exit at 3 kA is less than 15% of local Ohmic input. Radiation induced Teflon ablation is unlikely as at this power level (approximately 2 x 10 6 W/m with the exit electrical field given in figure 9(b)) Teflon will not reach its melting point for the experimental duration of 7 ms [45]. The measured arc voltage at 3 kA (figure 8) remains the same as that of 2 kA within experimental error, which indicates that ablation is unlikely to take place.…”
Section: Characteristics Of Nozzle Air Arc With Radiation Dominated Amentioning
confidence: 77%
“…Any molten material is quickly heated to the boiling temperature and turned into vapor. Thus, the liquid layer attached to the electrode surface is very thin and can be neglected [17], [18]. The calculation of the rate of evaporation can be greatly simplified [ (13) and (17)].…”
Section: Arc-electrode Interfacementioning
confidence: 99%
“…Murphy [29] has shown that, with the assumptions of LTE and LCE, a combined diffusion coefficient can be used to describe the diffusion of species belonging to one gas in a mixture of two gases. The laminar diffusivity and turbulent diffusivity are, respectively, related to the local molecular viscosity and turbulent viscosity by (18) where and are, respectively, the molecular viscosity [25] and turbulent viscosity and , respectively, the laminar and turbulent Schmidt number. The magnitude of and are around unity [30] and we set in the present work.…”
Section: Materials Functionsmentioning
confidence: 99%
“…3, when the current waveform is the same and the peak current increases, the length of the fusion section becomes smaller, its proportion of etch pit depth becomes lower also. Some experimental results indicate that when the peak current is big (several hundreds kA), liquid metal material only is a very thin layer [14,21], and it is usually ignored, as summarized in the paper conclusions. This phenomenon is formed because when the current is very big, the external energy within unit time is much more than the energy of internal conduction, that is, injected heat fluxes of the vaporization front are much more than those of the fusion front, and the energy required for fusion is about 1/25 of that for vaporization, so after fusion, electrode material will vaporize in a very short time and depart from the electrode surface, and it is hard to accumulate and form a very long fusion section.…”
mentioning
confidence: 86%